Unreliable information and fear: Barriers to vaccination among IBD patients in China - Jingwen Liu; Zelin Yan; Wen Hu; Shuyan Li; Yan Chen (Human Vaccines & Immunotherapeutics)
Vaccination plays a crucial role in safeguarding individuals with inflammatory bowel disease (IBD) from potential epidemics. In light of the resurgence of COVID-19 in China, unvaccinated IBD patients are vulnerable to infection and potentially serious complications. The aim of this study is to assess the vaccination uptake and willingness among IBD patients, as well as to explore the factors influencing their decision to decline vaccination. An online questionnaire was distributed and analyzed. Bivariate analyses and logistic regression models were used to identify relevant factors. Two hundred and three patients from 243 non-vaccinated respondents were included in the analysis. A total of 167 (82.3%) respondents continued to decline vaccination, with individuals holding stable employment and higher family income displaying significantly lower intent (p < .05). The primary factors contributing to their hesitancy were misinformation and apprehension regarding potential side effects. Obtaining vaccine information from online sources, particularly text-based content, and apprehensions surrounding the adverse effects of COVID-19 vaccination were also found to significantly diminish willingness to receive the vaccine (p < .01). The present study revealed that unreliable information about vaccines is a key factor of hesitancy among non-vaccinated IBD patients. Making efforts to spread true information about the COVID-19 vaccine is of great importance.